The phylloplane yeast Pseudozyma: a rich potential for biotechnology. Issue 5 (8th August 2019) - Kitamoto, Hiroko
ABSTRACT: Basidiomycetous yeast Pseudozyma strains are often isolated from leaf surfaces. Here, we describe the sources of Pseudozyma yeasts and their useful secreted products, including enzymes and biosurfactants. We then outline the life of Pseudozyma on the leaf surface and introduce studies to verify ecological functions of their useful products. In addition, the function of Pseudozyma in maintaining the health of plants is briefly explained. Finally, the gene manipulation techniques necessary for future research and development of technological applications of Pseudozyma are described. Abstract : The yeast Pseudozyma produces enzymes and glycolipids useful for human life. This minireview introduces lifestyle of the yeast on leaf surfaces and its ecological functions.